Policies and policy processes of the European Union - Buonanno, Laurie; Nugent, Neill (Palgrave Macmillan, 2013)
"This major new text on EU policy-making provides a concise but systematic introduction to the main policy areas in which the EU is active and the way in which EU policy is made, explaining how and why the EU's policy portfolio has developed as it has and the distinctive characteristics of each broad policy area."--Publisher's website.